Impact of revised RG 1.183 on source terms and radiological consequences of rod ejection accident for the HRP1000 reactor - Yichen Chen; Changdong Lu; Zewu Zhao; Pingting Jiang; Chao Yu (International Journal of Advanced Nuclear Reactor Design and Technology, 2025)
This paper compares and analyzes the impact of the revised RG 1.183 on the source term and radioactive consequences of the rod ejection accident. The revision of RG 1.183 has resulted in changes to key assumptions in the source term analysis of the rod ejection accident, including the release fractions of fission products from the fuel rod plenum and gap, the release fractions from the molten fuel rod, as well as the primary-to-secondary leakage rates of the SG. The analysis shows that, based on the typical radial average fuel enthalpy increase after a rod ejection accident in the HRP1000, the revised RG 1.183 leads to a slight increase in the dose consequences for the public at the site boundary via the containment release pathway, while the dose consequences via the secondary system release pathway are slightly reduced. Additionally, the dose consequences of the rod ejection accident are positively correlated with the radial average fuel enthalpy increase. However, even if the radial average fuel enthalpy increase rises to 70 cal/g, the radioactive consequences still meet the acceptance criteria for design basis accidents as specified in GB 6249–2025.